EPR spectroscopy of irradiated bioactive glasses - Padlyak, B.; Szarska, S. (Functional Materials, 2004)
The X-band (v = 9.4 GHz) EPR spectra of the UV-, X-, and y-irradiated biologically active glass (Bioglass) samples of two different compositions have been investigated at 7 7 and 300 K. The generation efficiency of the electron and hole centers depends strongly on the basic Bioglass composition and is almost independent of ionizing radiation type and presence of the non-controlled Fe3+ impurity in the glass structure. Influence of pre-treatment in NaCI solution and simulated body fluid on formation processes of the radiation-in -duced paramagnetic defects in Bioglass have been investigated. Spin Hamiltonian parame -ters and thermal stability of the radiation-induced centers have been evaluated. Electron structure, formation peculiarities and possible